2003
DOI: 10.1097/01.tp.0000092496.05951.d5
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor receptor type II 196M/R genotype correlates with circulating soluble receptor levels in normal subjects and with graft-versus-host disease after sibling allogeneic bone marrow transplantation1

Abstract: Because sTNFRIIs can act as TNF antagonists, the association between recipient and donor TNFRII 196R allele status and acute or extensive chronic GVHD incidence, respectively, may reflect reduced circulating sTNFRII.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
4

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 28 publications
3
31
2
4
Order By: Relevance
“…A polymorphism (196 R/M) in the TNF receptor II gene in HLA-matched unrelated HSCT found that recipients of TNFRII-196R-positive donors had a higher incidence of severe GvHD and a lower rate of relapse than from TNFRII 196 M homozygous donors (Ishikawa et al, 2002). The recipient TNFRII 196R allele was associated with acute GvHD incidence but the TNFRII 196RR genotype in the donor was associated with (increased) incidence of extensive chronic GvHD in an HLA-matched sibling HSCT cohort (Stark et al, 2003).…”
Section: Tnf Genesmentioning
confidence: 98%
See 2 more Smart Citations
“…A polymorphism (196 R/M) in the TNF receptor II gene in HLA-matched unrelated HSCT found that recipients of TNFRII-196R-positive donors had a higher incidence of severe GvHD and a lower rate of relapse than from TNFRII 196 M homozygous donors (Ishikawa et al, 2002). The recipient TNFRII 196R allele was associated with acute GvHD incidence but the TNFRII 196RR genotype in the donor was associated with (increased) incidence of extensive chronic GvHD in an HLA-matched sibling HSCT cohort (Stark et al, 2003).…”
Section: Tnf Genesmentioning
confidence: 98%
“…now been associated with GvHD and HSCT transplant outcomes (Brok et al, 1998;Fishman et al, 1998;Middleton et al, 1998;Cavet et al, 1999Cavet et al, , 2001Grainger et al, 1999;Cullup et al, 2001Cullup et al, , 2003Socié et al, 2001;Hattori et al, 2002;Ishikawa et al, 2002;Kögler et al, 2002;Rocha et al, 2002;Lin et al, 2003;MacMillan et al, 2003a;Stark et al, 2003;Keen et al, 2004).…”
Section: Il-10mentioning
confidence: 99%
See 1 more Smart Citation
“…88 Recipient IL-1Ra polymorphisms associated with lower production of IL-1Ra, and thus perhaps more biologic activity of IL-1 were also associated with chronic GVHD. 86 Recipient IL-6 polymorphisms have been associated with chronic GVHD in 2 reports, 89,90 though these studies failed to find an association with other donor or recipient polymorphisms (TNF-␣, TNF-␤, IL-1, IL-10, IFN-␥). A study by Stark et al 90 identified an association between chronic GVHD and donor homozygosity for the 196R allele of the TNF type II receptor (TNFRII), associated with decreased TNFRII levels and thus increased functional levels of TNF.…”
Section: Cytokine Therapymentioning
confidence: 99%
“…86 Recipient IL-6 polymorphisms have been associated with chronic GVHD in 2 reports, 89,90 though these studies failed to find an association with other donor or recipient polymorphisms (TNF-␣, TNF-␤, IL-1, IL-10, IFN-␥). A study by Stark et al 90 identified an association between chronic GVHD and donor homozygosity for the 196R allele of the TNF type II receptor (TNFRII), associated with decreased TNFRII levels and thus increased functional levels of TNF. Eternacept, a recombinant soluble TNF inhibitor, has reported activity in 10 steroid-refractory patients with chronic GVHD.…”
Section: Cytokine Therapymentioning
confidence: 99%